"Are you going to come and see us again soon?" An intergenerational event between stroke survivors and school-children. (12th December 2016) - Lane, Kathleen
Abstract : Purpose: A one-hour intergenerational event held at an infant school in Norfolk, England, aimed to increase the citizenship experience of young children and their awareness of what it means to live with stroke, and to address social isolation or self-confidence in communicating among stroke survivors with aphasia. It was also intended to gauge whether this activity might provide a basis for future research. The paper aims to discuss these issues. Design/methodology/approach: Four community-dwelling stroke survivors with aphasia were recruited. In total, 12 pupils aged six and seven were selected by their Year 2 teacher and head-teacher. At the event, participants sat in groups of one adult and three pupils and engaged in writing, hand-tracing and talking about pictures. The author circulated among the groups to facilitate engagement. Findings: All participants enjoyed interacting together in the activities. The pupils gained insights into the stroke survivors' lived experience and wanted them to return to "see us again soon"; the adults valued being in the "real world" and practising their conversation in activities different from their usual routines. Feedback indicated the value of the engagement and that participants welcomed similar intergenerational opportunities. The author will develop a research application exploring enablers, barriers and benefits of this type of engagement. Originality/value: The event gave a rare opportunity for stroke survivors with aphasia to participate in intergenerational activities and for children to engage with vulnerable older adults. It demonstrated the value of interactions in which learning and insights are obtained on both sides. It also provided evidence that pursuing research in this field is feasible.